Transmission of Staphylococcus aureus in the anaesthesia work area has greater risk of association with development of surgical site infection when resistant to the prophylactic antibiotic administered for surgery. (April 2023) - Loftus, R.W.; Dexter, F.; Brown, J.R.
Summary: Background: The extent to which the transmission of prophylactic-antibiotic-resistant bacteria from the anaesthesia work area increases the risk of surgical site infection (SSI) is unknown. It was hypothesized that the risk of SSI would increase progressively from no transmission to transmission of prophylactic-antibiotic-resistant isolates. Methods: This was a retrospective analysis of archival samples collected in two previously published studies with similar inclusion criteria and sample collection methodology (observational study 2009–2010 and randomized trial 2018–2019). Archival isolates were linked by barcode to all patient demographic and procedural information, including the prophylactic antibiotic administered, transmission and development of SSI. For this study, all archival isolates underwent prophylactic antibiotic susceptibility testing, and the ordered association of transmission of Staphylococcus aureus (no transmission, transmission of prophylactic-antibiotic-susceptible isolates and transmission of prophylactic-antibiotic-resistant isolates) with SSI was assessed. Results: The risk of development of SSI was 2% (8/406) without S. aureus transmission, 11% (9/84) with transmission of S. aureus isolates that were susceptible to the prophylactic antibiotic used, and 18% (4/22) with transmission of prophylactic-antibiotic-resistant S. aureus isolates. The Cochrane–Armitage two-sided test for ordered association was P <0.0001. Treating these three groups as 0, 1 and 2, by exact logistic regression, the odds of SSI increased by 3.59 with each unit increase (95% confidence interval 1.92–6.64; P <0.0001). Conclusions: Transmission of S. aureus in the anaesthesia work area reliably increases the risk of SSI, especially when the isolates are resistant to the prophylactic antibiotic administered.